Information Literacy and Academic Performance among Secondary Level Student Teachers in Aided Teacher Education Colleges: Investigating Information Literacy among Secondary Level Student Teachers in Aided Teacher Education Colleges (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Information Literacy is a vital skill for twenty-first-century teachers and students in all higher education. Accessing information is a fundamental right for people, and Information Literacy is essential for them to apply this right. Individuals who are well-informed about finding, evaluating, analyzing, integrating, managing, and conveying information to others efficiently and effectively are successful in life. Information literate students, faculty, and the general public were most efficient for answering queries, providing clarifications, and budding new concepts and thoughts for the future. The present investigation aimed to examine information literacy among secondary level Student Teachers. The method adopted for the collection of data from different Aided Teacher Education colleges was Normative Survey.